Developing the adaptive materials based on learning style to increase student's conceptual understanding - Lukman Hakim; Patricia Hotma Minar Lubis; Wacharaporn Khaokhajorn (Universitas Negeri Yogyakarta, 2022)
This study aimed to develop an adaptive electrical material based on Felder Silverman's learning style that can improve students' conceptual understanding. The method used in this research was the ADDIE research and development method which consists of the analysis, design, development, implementation, and evaluation stages. The data were gathered using learning style tests, concept understanding tests, and questionnaires. The data were then analyzed using descriptive analysis and N-gains. The analysis of the improvement of electrical learning outcomes used normalized gains. Based on the explanation, it can be concluded that the dominant student learning style characteristics are visual and sensing. The test results of the quality of electrical teaching materials with an average of 85.38 categories are very feasible. The results of the conceptual understanding test of students who received adaptive electricity material with an average N-gains of 0.7 categories were very high. The highest N-gains are students with visual and verbal learning styles, namely, 0.72. Based on the combination of the Felder Silverman learning style model, it is 0.73 for students with visual sensing learning style types.